Improvement of vermicompost produced from POME sludge on selected soil physicochemical properties and the physiological performance of maize - Mohd Zulkefly, Afieqah (2022)
Palm oil industries is one of the world’s leading producer in Malaysia which is contribute to the Malaysian agricultural sector. However, palm oil production generates abundance of Palm Oil Mill Effluent (POME) sludge wastes eventually pollute the environment. Sludge waste from the palm oil were treated to produce treated POME sludge (TPS). The waste sludge were treated with specific hydraulic retention time and the standard methodologies of the wastewater that use as raw material for vermicomposting. Vermicomposting is one of the methods to treat the waste with minimal cost. A research was conducted in an open field at Agrotech farm, Universiti Putra Malaysia from June to September 2019. The treatments were: (T1) control (NPK fertilizer), (T2) 1 kg of vermicompost + NPK, (T3) 2 kg vermicompost + NPK, (T4) 1 kg TPS + NPK and (T5) 2 kg TPS + NPK with 5 replications. Vermicompost used in this experiment were produced from treated POME sludge (TPS). Half recommendation rate of NPK fertilizer were applied. The experimental design were laid in a randomized completely block design (RCBD). The first objective of the research was to examine how TPS and vermicompost affect the physicochemical characteristics of the soil. The results showed that 2 kg vermicompost + NPK influence the soil physicochemical properties significantly (p < 0.05) while control treatment showed least effect to the soil physicochemical properties. This was due to the improved of soil texture and structure thus enhanced soil shear strength which were resulted in the increased angle of internal friction and low cohesion value. Vermicompost have higher total N, P, K Ca and Mg compared to chemical fertilizer and TPS. The ability of vermicompost to retains adequate nutrients supply due to the movement of water through its effect on the physical characteristic of soils. The second objective aimed to evaluate physiological performance of maize after application of vermicompost and treated POME sludge (TPS). The 2 kg vermicompost had higher chlorophyll content which contributed to the increased rate of photosynthesis. Maize applied with vermicompost showed increase the maize growth compared to maize applied with NPK fertilizer due to the dry matter production, crop performance analysis and root weight density increased significantly using 2 kg of vermicompost treatment. In conclusion, the research showed that the influence of vermicompost giving highest growth parameters and improved the soil physicochemical properties. The treated POME sludge (TPS) are capable to use for production of vermicompost.